Achieving superior high-temperature mechanical properties in Al-Cu-Li-Sc-Zr alloy with nano-scale microstructure via laser additive manufacturing - Yang Qi; Hu Zhang; Xu Yang; Yilong Wang; Changjun Han; Wei Fan; Jiawei Liang; Haihong Zhu (Materials Research Letters, 2024)
Traditional aluminum alloys are unsuitable for structural use above 200 ℃ due to precipitate coarsening or dissolution. Laser powder bed fusion (LPBF) additive manufacturing technique enables fabricating novel aluminum alloys with enhanced high-temperature properties. This study focuses on investigating the mechanical properties and microstructural evolution of a novel LPBF-fabricated Al-Cu-Li-Sc-Zr alloy at elevated temperatures. The microstructure is characterized by nano-scale grains and precipitates. Excellent grain structure and precipitate stability result in superior high-temperature mechanical properties. This study advances additively manufactured aluminum alloy design for potential high-temperature applications, offering valuable insights into their behavior in extreme environments.